2016
DOI: 10.5966/sctm.2015-0199
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells and Mononuclear Cells From Cord Blood: Cotransplantation Provides a Better Effect in Treating Myocardial Infarction

Abstract: The aim of this study was to evaluate the effect of cotransplanting mononuclear cells from cord blood (CB-MNCs) and mesenchymal stem cells (MSCs) as treatment for myocardial infarction (MI). Transplanting CD341 cells or MSCs separately has been shown effective in treating MI, but the effect of cotransplanting CB-MNCs and MSCs is not clear. In this study, MSCs were separated by their adherence to the tissue culture. The morphology, immunophenotype, and multilineage potential of MSCs were analyzed. CB-MNCs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The study selection process is shown in Figure S1. We identified a total of 1483 records, and 25 reports were included in the final analysis. , Two publications were from the same original study and their data were pooled. , Thus, 24 studies, including 15 RCTs and 9 observational studies, were included. These studies were published between 2019 and 2023 and enrolled a total of 12,413 patients (6175 in the SGLT2i group and 6238 in the non-SGLT2i group).…”
Section: Resultsmentioning
confidence: 99%
“…The study selection process is shown in Figure S1. We identified a total of 1483 records, and 25 reports were included in the final analysis. , Two publications were from the same original study and their data were pooled. , Thus, 24 studies, including 15 RCTs and 9 observational studies, were included. These studies were published between 2019 and 2023 and enrolled a total of 12,413 patients (6175 in the SGLT2i group and 6238 in the non-SGLT2i group).…”
Section: Resultsmentioning
confidence: 99%
“…Our study quantitatively assesses the effect of co-transplanted MSC on survival and therapeutic effect of iPS-CM by serially and non-invasively monitoring the retention kinetics of viable luciferase-expressing CM using BLI and cardiac function via MRI. Among previous studies comparing the effects of single and combined cell therapies in animal models of MI (41,(43)(44)(45)(46)(47)(48)(49), only Kearns-Jonker et al investigated the added benefits of MSCs and ESC-derived CMs in a rat model of MI but they did not quantify cell retention (45). Ye and coworkers used quantitative PCR (qPCR) to assess cell retention in their study comparing therapeutic effects of human iPS-CM alone or in combination with iPSC-derived endothelial cells and smooth muscle cells in a pig model of ischemia/reperfusion injury (41).…”
Section: Discussionmentioning
confidence: 99%
“…Mononuclear cells were isolated from 5 ml of peripheral blood (before and after moving to the plateau, 3,700 m) by using lymphocyte separation medium (Solarbio, Beijing, China), as previously described ( Chen et al, 2016 ). Total RNA was extracted from 10 7 mononuclear cells using TRIzol Reagent (Invitrogen, Carlsbad, CA, USA) according to the manufacturer’s protocol and then quantified using a UV-2550 spectrophotometer (Shimadzu, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%